LIVE WELL EVERY DAY : Your plan for a happy body and mind - George, Alex, Dr. (London : Aster, an imprint of Octopus Publishing Group Ltd, 2021)
What can you change today, and not put off until tomorrow? Dr Alex is on a mission to empower us to make our own health choices, take positive control and feel equipped and inspired to make those small changes today that energise and future-proof for life. 'Health and happiness come from the cumulative effects of many small and positive daily changes to our lifestyle. It's about building sustainable and healthy habits - taking small and purposeful steps to a healthy future. By the end of the book, I hope my readers have developed their own "bespoke health toolkit" to be used across every aspect of their lives, and to make long-lasting and meaningful change. What you do consistently has a direct impact on your day-to-day health, your immune system, your mental health, your metabolism, your bone density, your heart health, your blood pressure, your energy levels and how you fight disease generally. Your lifestyle is often your body's biggest support system and the more robust you can make that the more you can rely on it to get you through every day. Think of it like your life insurance policy. Live Well Every Day addresses the very modern health challenges of today's world - anxiety; social pressure and mental health; immune system health; how to be fit, flexible and eat well in a sedentary world; sexual health; gut health and more... Get the facts, pick your goals and take action with Dr Alex. Small changes. Big results
Includes index
"7 simple steps to a healthier life"--Cover
Keywords: Self-care, Health; Health